STRATEGI KOMUNIKASI KOLABORATIF KOMISI INFORMASI PROVINSI JAWA BARAT DALAM PENGUATAN KETERBUKAAN INFORMASI PUBLIK DI TINGKAT PEMERINTAH DAERAH - Muhammad Farid; Dedy Djamaluddin Malik; Anton Sulaiman (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2025)
Public information disclosure constitutes a fundamental element in realizing transparent, accountable, and participatory governance. This study analyzes the collaborative communication strategy of the Komisi Informasi Provinsi Jawa Barat (West Java Provincial Information Commission) in strengthening the implementation of public information disclosure at the regional government level. Based on Karl E. Weick’s Organizational Information Theory, this research examines how collaborative communication processes contribute to sensemaking, reduce information ambiguity, and create adaptive communication systems within the regional bureaucratic environment. This study employs a descriptive qualitative method with a case study approach, utilizing interviews, observations, and analysis of official documents issued by the West Java Information Commission. The findings indicate that the Commission’s collaborative communication strategy operates through three main stages: enactment (the construction of meaning and problem identification), selection (the determination of effective communication strategies), and retention (the institutionalization of sustainable communication practices). Through integrated Public Information Officer (PPID) forums, public mediation processes, and digital campaigns, the West Java Information Commission has successfully strengthened cross-sector coordination and fostered a culture of transparency within regional government institutions. This study concludes that collaborative communication functions not only as an instrument of coordination but also as a mechanism of organizational learning that enhances public participation and trust in information institutions.